2019
DOI: 10.1002/ccd.28164
|View full text |Cite
|
Sign up to set email alerts
|

Degree of valve calcification in patients undergoing transfemoral transcatheter aortic valve implantation with and without balloon aortic valvuloplasty: Findings from the multicenter EASE‐IT TF registry

Abstract: Aims We aimed to assess whether the level of aortic root calcification is associated with BAV performance/omission during transcatheter aortic valve implantation (TAVI), and to explore related outcomes. Methods and results EASE‐IT TF was a prospective, observational, multicenter registry of patients undergoing TF‐TAVI with the Edwards SAPIEN 3, with or without BAV predilation. Valvular calcification was quantified from pre‐procedural multi‐slice computed tomography images and compared between BAV and no BAV pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The design and rationale of EASE-IT TF have been previously described 12 13. Patients undergoing TF-TAVI at 10 experienced sites were enrolled between May and November 2016 and the patient followed throughout 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and rationale of EASE-IT TF have been previously described 12 13. Patients undergoing TF-TAVI at 10 experienced sites were enrolled between May and November 2016 and the patient followed throughout 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for calcium assessment were described previously 13. In short, a routine multi-slice computed tomography (MSCT) scan performed prior to TAVI was obtained for each patient as per local practice.…”
Section: Methodsmentioning
confidence: 99%
“…Although the absence of predilatation did not increase the post-dilatation rate in the DIRECTAVI trial using balloon-expandable THV, the post-dilatation rate was reported with a two-fold increase in the direct trial following the direct implantation of a self-expandable THV [ 41 ]. It might also be necessary to use pre-dilatation to cross the valve in patients with very tight stenosis with greater degrees of calcification, as reported in the recent EASE-IT TF registry and in the DIRECTAVI trial [ 42 , 43 ]. Other anatomic factors, including calcified bicuspid valves, horizontal arch and/or femoral tortuosity, may indicate crossing difficulties in the absence of pre-dilatation [ 42 ].…”
Section: Direct Implantation Of the Thvmentioning
confidence: 99%
“…In this edition of Catheterization and Cardiovascular Interventions (CCI), Butter et al, reports their findings from the EASE‐IT TF study, a prospective, two‐armed, controlled‐cohort, observational registry in patients with pre BAV versus direct TAVR using Edwards Saphien 3 valve platform. Although the number of patients in BAV group ( n = 55) are much smaller than the ones with direct TAVR ( n = 123), this interesting study gives some lights into the discussion of BAV prior to TAVR.…”
mentioning
confidence: 99%
“…Few previous studies also compared TAVR with BAV versus direct TAVR without looking into the above valvular heavy calcification volumes by CT. The only randomized controlled trial which was recently published by Toutouzas et al, the DIRECT trial (171 patients were randomized at four centers), proved that direct TAVR is non‐inferior to TAVR with pre‐BAV regarding procedure success, periprocedural mortality, stroke, new permanent pacemaker implantation, vascular complications, and 1‐year mortality . Several centers still prefer to perform BAV before implantation in cases of ambiguous sizing on CT, assessment of coronary ostia coverage with borderline ostia height, fear of device entrapment below the aortic valve or anticipated need for lengthy positioning maneuvers, especially when AVA < 0.5 cm 2 .…”
mentioning
confidence: 99%